Analisis Teori Darwin Ditinjau dari Konsep Waktu - Karmana, I Wayan (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2023)
The development of a science cannot be separated from the development of technology, as well as the development of the theory of evolution as a branch of pure biology which studies the existence of changes in the structure of living creatures which until now continues to experience development. This article uses a literature review approach by examining Darwin's theory of evolution based on the philosophy of science in the study of past, present and future time. Darwin's theory is striking in the excellence of its findings, such as the development of empirical data on an organism, even though it has had many controversies in the development of its science. The results of the study and analysis show that Darwin's theory of evolution can still be used today and is compatible with other existing theories.